Elatostema longicadatum Grierson & long (Urticaceae) an addition to the Flora of India and Burma - Jain, S. S.; Gaur, R. C. (Indian Forester, 1985)
Forests on northern and southern aspects at Siahi Devi hill of West Almora Division in Kumaun Himalayas were quantitatively analysed. Three forest types, viz. Pinus roxburghii at hill base (1,250-1,500 m), mixed oak-pine at higher altitude (1.750 m) and Quercus leucotrichophora at hill top (2.000-2.200 m) were recognized on northern aspect. Forests on southern aspect were categorized only into two types. Viz. P. roxburghii upto 2,000 m and mixed oak-pine at hill top (2,200 m). The composition of tree layer among the forests differed markedly on northern aspect whereas it was considerably similar on southern aspect. Shrub layer indicated dissimilarity among forests on both the aspects. Tree species richness and diversity were maximum in Q. leucotrichophora forest on northern aspect and in oak-pine forest on southern aspect. Concentration of dominance showed an inverse relation with diversity Q. leucotrichophora indicated fair regeneration potential in the studied forest sites. P. roxburghii exhibited faster regeneration than Q. leucotrichophora and it may expand replacing the latter tree Species.